Grass-root coaches knowledge, understanding, attitude and confidence to deliver injury prevention training in youth soccer: a comparison of coaches in three EU countries - Croix, M. D. S.; Ayala, F.; Sanchez, S. H.; Lehnert, M.; Hughes, J. (Journal of Science in Sport and Exercise, 2020)
Purpose: It is well recognised that injury prevention training can reduce injury incidence, however current coach education pathways do not provide grass-root coaches with the knowledge and confidence to deliver such training to youth players. The aim of this study was to explore differences in knowledge, understanding, attitude and confidence to deliver such injury prevention training in three European countries. Methods: A total of 269 grass-root soccer coaches from 3 European countries (Czech Republic, UK, Spain) were recruited for this study. A validated questionnaire exploring knowledge, understanding, attitude towards and confidence to deliver youth injury prevention training was completed prior to a 2 h workshop on injury prevention training. Differences between countries was examined using Bayesian factors to quantify the evidence for and against the hypothesis of independence (H0) by assuming a Poisson sampling scheme (as there was no a priori restriction on any cell count, nor on the grand total) (BF10 Poisson). Results: Current knowledge, attitude and confidence to deliver injury prevention training to youth players was poor across all three European countries. Relatively few coaches were currently using injury prevention training in their coaching sessions (23%). There were some country specific differences for attitude towards injury prevention training and confidence to deliver injury training, with Spanish coaches reporting a more positive attitude and confidence to deliver such training. Significantly fewer coaches in the UK were using injury prevention training compared to coaches in Spain and the Czech Republic. Conclusion: As coaches identified a need for coach education and few were delivering injury prevention training, there is a clear need to embed and implement this programme into the grassroots coaching framework of sports governing bodies to improve adoption, implementation and maintenance.